MAKNA REFLECTIVE TEACHING DALAM PENGALAMAN MENGAJAR GURU-GURU BERPRESTASI (STUDI ANALISIS FENOMENOLOGIS INTERPRETATIF) - , ALI MAHMUD ASHSHIDDIQI, Prof. Dr. Amitya Kumara, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Teaching is one of the teacher's work which is the most complex and often challenging, which requires a lot of professional skills in making decisions and resolving a variety of problems related to learning and teaching. Ironically, the fact is there are many phenomenons of unprofessionality in the work of teachers, such as teacher-proof curriculum, technical rationality view, and simplicity myth. These caused the underestimating that teaching is too easy and simple, and suggest the uncritical practices to teachers. Otherwise, most studies about teaching have pointed out that reflection is a practice which encourage professionalism of teachers. Reflective practice became an important part in the theachersâ professional development. This qualitative study used the theories of reflective teaching as theoretical perspective framework to examine the teaching experience of outstanding teachers. The author conducted this study by way of involving four outstanding teachers as participants. They represent four different educational units, that is to say: kindergarten, elementary school, junior high school and senior high school. The outstanding teachers were be angaged in current study because of their effectivity in many classrooms as earlier studies have examined and showed it. This study aimed to describe articulation of the outstanding teachers about their teaching experiences, and to explore the meanings of reflective teaching contained in the experiences. Both semi-structured interviews and documentation method were utilized to collect data. After the self-reported data has been collected, it was then be analyzed and interpreted through the procedure of interpretative phenomenological analysis (IPA), as a perspective in qualitative research which is based on the theoretical underpinnings of phenomenology, hermeneutics, and idiography. IPA is an interpretative endeavour which committed to the detailed examination of how someone makes sense of his or her major subjective life experience. Qualitative data analyses revealed that there were reflective practices in teaching experience of the participants, in terms of nine primary focuses in reflective teaching, namely focus on: values, knowledge, experience, completion of tasks/jobs, problems and decisions/actions, environment, collegiality, examination/investigation, and reflection. Reflective practices became the subject of major discussion of this study, before the author conclude that taken together those practices indicate the meanings of reflective teaching in the teaching experience of the outstanding teachers.